Genetic analysis in pre-breeding lines derived from inter sub-specific cross of blackgram (Vigna mungo (L.) Hepper) - S. Manju Devi1, M. Kumar*2, P. Jayamani1, K. R. Latha3 and M. Muthamilan4 (Indian Society of Plant Breeders, 2021)
One hundred and eighty nine stabilised lines obtained from the cross VBN (Bg) 5 and Vigna mungo var silvestris 22/10 were evaluated during Rabi, 2019. Analysis of variance for various traits exhibited significant differences among the lines for all the nine quantitative traits. The GCV was lower compared to the values of PCV which revealed the influence of the environment in deciding the expression of these lines. Moderate GCV was recorded for single plant yield (16.22 %), the number of pods per plant (12.60%), plant height (12.48 %), the number of primary branches per plant (11.75 %) and hundred seed weight (11.34%). High heritability was observed for the characters like hundred seed weight (96.99 %), plant height (78.33 %), days to 50 per cent flowering (72.98 %), single plant yield (72.44 %) and pod length (65.70 %). High heritability along with high genetic advance as per cent of mean was observed for hundred seed weight (96.99, 23.00), plant height (78.33, 22.76) and single plant yield (72.44, 28.44) indicates the possibility of improving these traits by selection since there is a wide range of variation and additive gene action exists for these traits. The maximum number of lines with a positive value over the mean was observed for pod length and 100 seed weight. Correlation analysis showed that the number of pods per plant, plant height, the number of seeds per pod, the number of primary branches per plant, the number of pods per cluster, pod length and hundred seed weight had positive significant association with single plant yield. A number of pods per plant and pod length had a high positive direct effect on single plant yield. Hence, the selection for these characters would improve seed yield in blackgram.